Malaria Preventive Practices among Pregnant Women in Akwa Ibom State, Southern Nigeria - , T. Kasso; , I. L. Oboro; , O. Maduka; , A. T. O. Awopeju; , N. I. Paul; , L. E. Yaguo-Ide; , I. N. Chijioke-Nwauche; , M. Ogoro; , G. Otto; , C. A. Nwauche (Archives of Current Research International, 2020)
Background: Malaria is a serious public health problem in developing countries with Africa bearing most of its burden. Pregnant women are more susceptible to malaria and it is one of the leading causes of maternal and perinatal mortality/morbidity. Use of effective malaria preventive measures during pregnancy reduces its burden and complications. Aim: This was to determine malaria preventive practices used by pregnant women in Akwa Ibom state, Nigeria. Materials and Methods: It was a cross sectional study of pregnant women attending public and private health facilities in Akwa Ibom state. An informed written consent was obtained from the participants. Stratified sampling method was used in selecting the health facilities and the study participants. Information was obtained with pretested questionnaires by trained personnel with the aid of Open Data Kit (ODK) on android phones. Data was managed with SPSS 22.0 and P-value of <0.05 was considered statistically significant. Results: There were 935 participants in the study. Their mean age was 28.52 ± 5.09 years with 879 (94.0%) being married. Most had secondary and tertiary degrees: 451(48.2%) and 440(47.1%). Majority of them were traders/business women and self-employed (58.2%) while 7% were unemployed. Malaria preventive practices were use of window net, bed net and insecticides accounting for 659(71%), 447(48.2%) and 207(22.3%) respectively. There were 612 (65.5%) participants that received malaria drugs for prevention with 452(73.9%) receiving Intermittent Preventive Treatment in Pregnancy (IPTp) with Sulfadoxine-Pyrimethamine (SP). Only 296 (31.7%) of them slept under bed nets the night before the interview. Conclusion: Common preventive practices employed by pregnant women were IPTp with SP, window nets, ITNs and modified IRS. Majority of the women utilized widow nets, though not as effective as ITNs. Efforts should be intensified concerning awareness creation about the benefits of ITN use during pregnancy.